Development of information system for human's clinical and laboratory parameters analysis - Высоцкая, Елена Владимировна; Порван, Андрей Павлович; Улескина, Наталья Андреевна; Чепаю, Тапа Оливер (Technology audit and production reserves, 2015)
The article is devoted to the development of information system for human’s clinical and laboratory parameters analysis and processing that allowed to automate processing of the results of all kinds of laboratory tests (hematology, biochemical, immunological, cytological, microbiological), internal and external laboratory quality control. One of the main components of the information system is designed relational database that allows storing information in a convenient form and simplifies the work with documentation for technical personnel. The presence of the embedded modules of internal and external quality assessment of laboratory research allows enhancing the research quality by the systematic implementation of appropriate control with the construction of Yuden-Murakami, Levey-Jennings, Westgard charts, calculation of cumulative amounts, parallel samples, controlling the reproducibility of duplicates, the average normal values with the usage of Bull’s algorithm and SQC method. This makes it possible to take into account the effect of systematic and random errors, as well as biological and analytical variation on the results of clinical researches.